Short interfering RNA-mediated silencing of glutaredoxin 2 increases the sensitivity of HeLa cells toward doxorubicin and phenylarsine oxide - Lillig, Christopher Horst (National Academy of Sciences, 2004)
Glutaredoxin (Grx) belongs to the thioredoxin fold superfamily and catalyzes glutathione-dependent oxidoreductions. The recently discovered mitochondrial and nuclear Grx (Grx2) differs from the more abundant cytosolic Grx (Grx1) by its higher affinity toward S-glutathionylated proteins and by being a substrate for thioredoxin reductase. Here, we have successfully established a method to silence the expression of Grx2 in HeLa cells by using short interfering RNA to study its role in the cell. Cells with levels of Grx2 <3% of the control were dramatically sensitized to cell death induced by doxorubicin/adriamycin and phenylarsine oxide but did not show signs of a general increase in oxidative damage with respect to carbonylation and glutathionylation. The ED(50) for doxorubicin dropped from 40 to 0.7 μM and for phenylarsine oxide from 200 to 5 nM. However, no differences were detected after treatment with cadmium, a known inhibitor of Grx1. These results indicate a crucial role of Grx2 in the regulation of the mitochondrial redox status and regulation of cell death at the mitochondrial checkpoint.